A Search Model of Marriage with Differential Fecundity - Eugenio P. Giolito (Institute for the Study of Labor (IZA), 2004)
It is commonly observed that over time and across societies, women tend to marry older men. The traditional explanation for this phenomenon is that wages increase with age and hence older men are more attractive in the marriage market. This explanation, however, involves an implicit assumption about female specialization in home production - an assumption that does not completely hold, especially in modern times. This paper shows that a marriage market equilibrium where women marry earlier in life than men can be achieved without making any assumptions about the wage process or gender roles. The only driving force in this model is the asymmetry in fecundity horizons between men and women. When the model is calibrated with Census Data, the average age at first marriage and the pattern of the sex ratio of single men to single women over different age groups mimics the patterns observed in developed countries during the last decade (e.g. France, the U.S. and Sweden).
Keywords: D83; J12; 330; marriage markets; search; sex ratio; Ehe; Suchtheorie; Geschlecht; Fruchtbarkeit; Overlapping Generations; Theorie